Perayaan Maulid PErspektif Sosiologi Agama - Saidun Derani (Buletin Al-Turas, 2006)
The celebration of MAulid is very related to Islamic aspects (dimentions). So it can mot be taken away from itssocial institution to maintain social solidarity. This celebration is a fact an dsocial behavior in certain communitythat becomes its social charecteristic and not contrasted with islamic teaching. This event an be analyzed thoough sociologicaltheory/approach, Symbolic interaction, and phenomenology.